Atmospheric Photo-oxidation of Diethyl Carbonate: Kinetics, Products, and Reaction Mechanism - Rimondino, Guido Noé (2020)
The rate coefficient for the gas phase of diethyl carbonate with chlorine atoms has been determined at 298 K using a relative method, employing ethyl formate and ethyl acetate as reference compounds. The experimental value, (1.0 ± 0.2) × 10-11 cm3 molecule-1 s-1, is in good correlation with the one estimated by the SAR (Structure-Activity Relationship) method. The photo-oxidation mechanism of diethyl carbonate initiated by chlorine atoms was also studied at 298 K and atmospheric pressure as a function of the oxygen partial pressure. The main products identified by infrared spectroscopy were CH3CH2OC(O)OCHO, CH3CH2OC(O)OCH2CHO, CH3CH2OC(O)OC(O)CH3, CO2, CO, HCOOH, and CH3COOH. The results reveal that the oxidation process occurs by the abstraction of a hydrogen atom from the methyl (43%) and methylene (57%) groups. The relative importance of each reaction path from the primary radicals formed in photo-oxidation and the identity of CH3CH2OC(O)OCHO, CH3CH2OC(O)OC(O)CH3, and CH3CH2OC(O)OCH2CHO were determined using computational methods. The activation energy of reaction paths for the main oxygenated radicals formed during photo-oxidation was determined using Gaussian09 Program.